Konsepsi dan Bentuk BUMDes dalam Peningkatan Kesejahteraan Masyarakat di Provinsi Jambi - Lili Naili Hidayah; Muskibah Muskibah; Ageng Triganda (Wajah Hukum, 2021)
This article discusses the concept and form of village-owned enterprises and sees how it plays a role as a way to increase the level of welfare of rural communities in Jambi Province and what are the challenges and obstacles in its implementation. The presence of this institution should be the right step in an effort to realize the welfare of the Village community, especially in the economic sector and in the context of developing rural communities, which are expected to reduce poverty. The provisions in the Village Law regarding implementing rules that want a business entity to reflect a village that has kinship and mutual cooperation and is confirmed in the Village Law that business entities owned by the village can later be legal or not legal but cannot be equated with legal entities commonly known. in the business world. Such as CV, PT and cooperatives. In the implementation of BUMdes, the problem of legal entities is often questioned by a third party when working together, so there are several obstacles to implementing BUMdes management.